Non-communicating rudimentary horn pregnancy managed at a community health center: a case report - Patel, Aastha H.; Nayak, Aniket B.; Patel, Jatin P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Pregnancy in a non-communicating rudimentary horn is a rare and potentially life-threatening form of ectopic pregnancy. Early diagnosis is challenging, particularly in low-resource settings, and delayed management often leads to rupture and massive hemorrhage. A 22-year-old G3P2L1D1 woman with two previous normal vaginal deliveries presented with two months of amenorrhea and spotting per vaginum. Ultrasonography suggested a left non-communicating rudimentary horn ectopic pregnancy of approximately 9 weeks’ gestation. Considering the high risk of rupture and limited diagnostic facilities, emergency laparotomy was performed at a community health centre. Intraoperatively, a left non-communicating rudimentary horn pregnancy was confirmed. Excision of the rudimentary. This case highlights that timely diagnosis and definitive surgical management of rudimentary horn pregnancy can be successfully achieved even at a community health center with limited resources, emphasizing the importance of clinical suspicion and prompt intervention.